Cages and clusters of Indium: spherical aromaticity? - Linti, Gerald W.; Bühler, Martina; Monakhov, Kirill; Zessin, Thomas (Modeling of molecular properties, 2011)
This chapter contains sections titled: Introduction Synthesis of Polyhedral Indium Clusters Quantum Chemical Calculations Summery References